Assessment of Functional Recovery and Subjective Donor-Site Morbidity Following Radial Forearm Flap Reconstruction in Small- to Moderate-Sized Palatal Defects. Issue 1 (March 2020) - Chandrappa, Ashok B.; Batth, Ritu S.; Vasudevan, Srikanth; Yellambalase, Anantheswar N. R.; Kumar, Pradeep N.; Reddy, Sudarshan; Seles, J. Nidya
Context: Palatal defects are encountered following tumor extirpation, trauma, or congenitally. Among the known alternatives, radial artery free forearm flap (RAFF) is a versatile flap that confers good results in head and neck reconstruction, but donor-site morbidity has been an issue of discontent among the plastic surgeons. This limitation needs to be studied further and addressed considering the unmatched quality of this tissue. Aims: This study aims to weigh the impact of the functional edge of this flap against the unpopular donor-site morbidity on a group of patients. Settings and Design: This is a retrospective analysis of recuperation of palatal function and patient concerns with the donor-site function and cosmesis on 7 consecutive patients with small-to-moderate palatal defects reconstructed with RAFF. Methods and Materials: Postoperative recovery of speech, palatal movement, and restoration of oromaxillary interface was assessed using objective tests, such as speech intelligibility testing and articulation studies. Simultaneously, subjective donor-site function and cosmesis were assessed using Patient Scar Assessment Scale (PSAS), Upper Extremity Functional Index (UEFI), and donor limb sensory testing. Results and Conclusion: Mean PSAS score was 8.28/60, and UEFI score reported was 77/80, which reflect high patient satisfaction with the donor site. Nasoendoscopy shows remarkable restoration of palate anatomy. Intelligibility testing depicts near-normal speech understandability, whereas articulation studies revealed distortions post-palatal reconstruction with RAFF. Radial artery free forearm flap should be considered as the forerunner of reconstruction in palatal defects involving less than 50%.